The growth-employment-poverty nexus in Latin America in the 2000s: Uruguay country study - Guillermo Cruces; Gary Fields; David Jaume; Mariana Viollaz (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
The Uruguayan story was one of declines in the early years of the 2000s in most indicators, followed by improvements in all of them. Economic growth was negative in the early years due to a severe economic crisis, positive and rapid thereafter except during the international crisis of 2008. Most labour indicators followed the same U-shaped pattern and were in 2012 at a better level than at the beginning of the decade, with the exceptions of labour earnings and some poverty indicators. The international crisis of 2008 slowed or stopped temporarily the improvements in some labour market indicators.
Keywords: O15; J01; J30; 330; Uruguay; Latin America; inclusive growth; labour market; poverty